Morphological Characterization of the Antennal Sensilla of the Afrotropical Sand Fly, Phlebotomus duboscqi (Diptera: Psychodidae). Issue 2 (2nd December 2020) - Bahia, Ana Cristina; Barletta, Ana Beatriz F; Pinto, Luciana Conceição; Orfanó, Alessandra S; Nacif-Pimenta, Rafael; Volfova, Vera; Volf, Petr; Secundino, Nágila Francinete Costa; de Freitas Fernandes, Fernando; Pimenta, Paulo Filemon P
Abstract: We investigated by scanning electron microscopy the morphology, distribution, and abundance of antennal sensilla of females Phlebotomus duboscqi sand fly, an important vector of zoonotic cutaneous leishmaniasis at Afrotropical region. Thirteen well-differentiated sensilla were identified, among six types of cuticular sensilla. The probable function of these sensillary types is discussed in relation to their external structure and distribution. Five sensillary types were classified as olfactory sensilla, as they have specific morphological characters of sensilla with this function. Number and distribution of sensilla significantly differed between antennal segments. The results of the present work, besides corroborating in the expansion of the morphological and ultrastructural knowledge of P. duboscqi, can foment future electrophysiological studies for the development of volatile semiochemicals, to be used as attractants in traps for monitoring and selective vector control of this sand fly.